Di Balik Bakti dan Patriarki: Double Burden pada Anak Perempuan Single Bekerja yang Tinggal Bersama Orang Tua - Nashriyah Ummuhany; Antari Ayuning Arsi (Universitas Hamzanwadi, 2026)
The condition of double burden among working women was not only experienced by married women but also by unmarried (single) daughters. This condition occurred when daughters bore the burden of supporting the family’s economy and carrying out domestic responsibilities at home. A cultural belief that domestic work is assigned to women because it has been socialized from an early age. This study aimed to examine the naturally experiences of double burden among single working daughters who lived with their parents and to identify the strategies they used to cope with this condition. A qualitative approach was employed, using the interactive data analysis technique proposed by Miles and Huberman. The results show that single daughters experience double burden mainly due to their family’s socio-economic conditions. Families with economic limitations tend to demand greater financial responsibility from daughters, so work orientation is emphasized not merely as an act of filial piety but also as an obligation imposed by parents. Family norms that justify domestic responsibilities as women’s natural duties also constitute a major factor contributing to the double burden experienced by daughters. To cope with this situation, daughters adopt two type of strategies. The first strategy aimed to cope domestic workloads, including sharing household tasks with other family members, also using domestic tools and paid services. The second strategy focused on cope the pressure resulting from the double burden, which included seeking recreation, finding a partner relationship, and obtaining social support.